Combination Therapy with Ciprofloxacin and Pentamidine against Multidrug-Resistant Pseudomonas aeruginosa: Assessment of In Vitro and In Vivo Efficacy and the Role of Resistance-Nodulation-Division (RND) Efflux Pumps - Megan Fletcher; Alex McCormack; Benjamin J. Parcell; Peter J. Coote (MDPI AG, 2023)
The aim of this work was to (i) evaluate the efficacy of a combination treatment of pentamidine with ciprofloxacin against Galleria mellonella larvae infected with an MDR strain of P. aeruginosa and (ii) determine if pentamidine acts as an efflux-pump inhibitor. Resistant clinical isolates, mutant strains overexpressing one of three RND efflux pumps (MexAB-OprM, MexCD-OprJ, and MexEF-OprN), and a strain with the same three pumps deleted were used. MIC assays confirmed that the clinical isolates and the mutants overexpressing efflux pumps were resistant to ciprofloxacin and pentamidine. The deletion of the three efflux pumps induced sensitivity to both compounds. Exposure to pentamidine and ciprofloxacin in combination resulted in the synergistic inhibition of all resistant strains in vitro, but no synergy was observed versus the efflux-pump deletion strain. The treatment of infected G. mellonella larvae with the combination of pentamidine and ciprofloxacin resulted in enhanced efficacy compared with the monotherapies and significantly reduced the number of proliferating bacteria. Our measurement of efflux activity from cells revealed that pentamidine had a specific inhibitory effect on the MexCD-OprJ and MexEF-OprN efflux pumps. However, the efflux activity and membrane permeability assays revealed that pentamidine also disrupted the membrane of all cells. In conclusion, pentamidine does possess some efflux-pump inhibitory activity, in addition to a more general disruptive effect on membrane integrity that accounts for its ability to potentiate ciprofloxacin activity. Notably, the enhanced efficacy of combination therapy with pentamidine and ciprofloxacin versus MDR P. aeruginosa strains in vivo merits further investigation into its potential to treat infections via this pathogen in patients.